Pengaruh Pelatihan Terhadap Kinerja Karyawan Koperasi Simpan Pinjam Sipakatallasa Kota Makassar : Penelitian - Edi Jusriadi; Zalkha Soraya; Alfisah Rusdian (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of human resource training on employee performance at the Sipakatallasa Savings and Loan Cooperative in Makassar City. The population in this study consists of all employees of the cooperative, totaling 35 individuals. The sampling technique used is total sampling, resulting in 35 respondents. Data collection methods include observation, questionnaires, interviews, and documentation. The data analysis methods used are descriptive analysis, instrument testing, classical assumption testing, and simple linear regression analysis. The results of the study indicate that, based on the t-test, training has a positive and significant effect on performance. The simple linear regression model shows that training is a factor that positively influences good performance; therefore, adequate training must be provided before good performance can be achieved.